Late presentation to HIV/AIDS care in Brazil among men who self-identify as heterosexual. - MacCarthy, Sarah (2016)
OBJECTIVE: To analyze the factors associated with late presentation to HIV/AIDS services among heterosexual men. METHODS: Men infected by HIV who self-identified as heterosexual (n = 543) were included in the study. Descriptive, biivariate and logistic regression analyses were performed to evaluate the factors associated with late presentation (defined as individuals whose first CD4 count was <350 cells/mm3) in the study population. RESULTS: The prevalence of late presentation was 69.8%. The multivariate logistic analysis showed testing initiated by the provider (OR adjusted 3.75; 95%CI 2.45–5.63) increased the odds of late presentation. History of drug use (OR adjusted 0.59; 95%CI 0.38–0.91), history of having sexually transmitted infections (OR adjusted 0.64; 95%CI 0.42–0.97), and having less education (OR adjusted 0.63; 95%CI 0.41–0.97) were associated with a decreased odds of LP. CONCLUSIONS:Provider initiated testing was the only variable to increase the odds of late presentation. Since the patients in this sample all self-identified as heterosexual, it appears that providers are not requesting they be tested for HIV until the patients are already presenting symptoms of AIDS. The high prevalence of late presentation provides additional evidence to shift towards routine testing and linkage to care, rather than risk-based strategies that may not effectively or efficiently engage individuals infected with HIV.